INTEGRATION OF SCIENCES IN MODERN SYNERGETIC DISCOURSE - Chaika, Yana (Global Prosperity, 2021)
Modern science and philosophy are entirely dependent on the globalization processes characteristic of modern socio-cultural space. Under such conditions, integration processes are an integral component of the development of any sphere of social life. Science has undergone a period of unification and unification, forming all the prerequisites for developing integration processes. The most appropriate methodology for the approval of interdisciplinary processes appears synergetics. Among interdisciplinarity distinguish academic integration of knowledge (multidisciplinarity and its varieties) and progressive (transdisciplinarity). The key goal of introducing the integration of the sciences is not the declarative unification but ensuring the two conditions of integration efficiency: the presence of a common subject (goal) of research and the formation of a common methodological arsenal for scientific research. The synergetic potential has not yet been fully disclosed among the scientific community. However, the issue of self-organization act as a promising tool for the scientific cluster of social life. Integration implies the dominance of a single science because bringing in knowledge from different sciences is dynamic and constantly changing. Therefore, the synergetic methodology, which demonstrates effectiveness in complex structures, allows for rapid and qualitative integration processes. The academic unification of the sciences does not yet demonstrate effectiveness since there is a clear need for dynamism. Transdisciplinarity under such conditions is the most progressive form of integration processes in science since this setting allows it to go beyond the framework of scientific disciplines. The blurring of the boundaries of academic disciplines allows the integration of methodologies, which ensures greater efficiency in conducting research and allows the development of new knowledge and theories. In fact, we are facing a new field of knowledge that encompasses all the available sciences and combines their potential for developing new knowledge.